CONTAMINATION IN NEWLY HATCHED LARVAE OF THE Ucides cordatus MANGROVE CRAB AND A NEW PERSPECTIVE ABOUT TRACE ELEMENTS TRANSPORT - Vianna de Almeida, Eduardo; Tavares Kütter, Vinicius; Vieira Silva-Filho, Emmanoel (Geochimica Brasiliensis, 2021)
Mangroves are relevant ecosystems due to their ecological role, economic use, and social importance. One of the most abundant and important species in Brazilian mangroves is the exploited crab Ucides cordatus. This species is the focus of the present study, whose aim was to evaluate the concentration of trace elements in the hepatopancreas of ovigerous females, eggs (pre-hatching and hatching stages), and for the first time, in newly hatched larvae. Ovigerous females were captured in two Southeastern Brazil mangroves (Guanabara Bay and Paraíba do Sul river secondary estuary) and spawning was held in spawning tanks, in the laboratory. Some females were not taken to the tanks but frozen right after collection. There was no significant difference in trace elements concentration between these females and those kept in the spawning tanks. Both essential and non-essential trace elements were detected in newly hatched larvae. Comparing with the adult female, the elements Zn, Cu, and Mn showed the highest concentrations in larvae and eggs. Vanadium, Cr, and Mn concentrations were significantly higher in hatching eggs then observed in newly hatched larvae, indicating the retention of elements in the eggshell. Considering the V (0.17 - 1.17 μg.g−1 dry weight), Cu (14.1 - 41.1 μg.g−1 dw), and Zn (235.4 - 263.9 μg.g−1 dw) concentrations in newly hatched larvae, which were similar to those observed in suspended particulate matter (SPM) and sediments in suspension, the planktonic larval dispersion could result in the transport of elements beyond the mangrove, and their introduction in coastal waters.